Venetoclax Shows Low Therapeutic Activity in BCL2-Positive Relapsed/Refractory Peripheral T-Cell Lymphoma: A Phase 2 Study of the Fondazione Italiana Linfomi - Ballotta, Laura; Zinzani, Pier Luigi; Pileri, Stefano; Bruna, Riccardo; Tani, Monica; Casadei, Beatrice; Tabanelli, Valentina; Volpetti, Stefano; Luminari, Stefano; Corradini, Paolo; Lucchini, Elisa; Tisi, Maria Chiara; et al. (Frontiers in Oncology, 2021)
Patients with relapsed/refractory (R/R) peripheral T-cell lymphoma (PTCL) have a poor prognosis, with an expected survival of less than 1 year using standard salvage therapies. Recent advances in our understanding of the biology of PTCL have led to identifying BCL2 protein as a potential therapeutic target. BLC2 inhibitor venetoclax was investigated in a prospective phase II trial in patients with BCL2-positive R/R PTCLs after at least one previous standard line of treatment (NCT03552692). Venetoclax given alone at dosage of 800mg/day, resulted in 1 complete response (CR) and 2 stable diseases (SD) among 17 enrolled patients. The majority of patients (88.2%) interrupted the treatment due to disease progression. No relationship with BCL2 expression was documented. At a median follow-up of 8 months, two patients are currently still on treatment (1 CR and 1 SD). No cases of tumor lysis syndrome were registered. Therefore, venetoclax monotherapy shows activity in a minority of patients whose biological characteristics have not yet been identified.